2023
DOI: 10.3390/f14020186
|View full text |Cite
|
Sign up to set email alerts
|

Key Characteristics of Forest Therapy Trails: A Guided, Integrative Approach

Abstract: Forest therapy is an emerging holistic health practice that uses multisensory immersive engagements in forest settings to achieve health and wellbeing outcomes. Many forest therapy engagements take place via slow walks along a trail to optimally experience the array of sensory phenomena afforded along the route, yet surprisingly few forest therapy studies to date have investigated the characteristics of forest sites and trails that give rise to healthful experiences. In this research, we employ a hybrid approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 312 publications
1
9
0
2
Order By: Relevance
“…However, the soundscape perception frequency with minimal discrepancy between current and expected sounds negatively predicted place identity, suggesting that the perception of such sounds may have impacted place identity similarly to its effect on residential satisfaction. The reason may be that people's minimal expected sound and noise overlap significantly, and noise is a major factor in choosing a place [51]. The research found that residents could form place identity through firsthand experiences, and individual activities were the result of practicing exercising subjectivity.…”
Section: Factors Influencing Residents' Place Identity In Residential...mentioning
confidence: 96%
“…However, the soundscape perception frequency with minimal discrepancy between current and expected sounds negatively predicted place identity, suggesting that the perception of such sounds may have impacted place identity similarly to its effect on residential satisfaction. The reason may be that people's minimal expected sound and noise overlap significantly, and noise is a major factor in choosing a place [51]. The research found that residents could form place identity through firsthand experiences, and individual activities were the result of practicing exercising subjectivity.…”
Section: Factors Influencing Residents' Place Identity In Residential...mentioning
confidence: 96%
“…plants, and investigating sustainable management strategies for forests used for therapeutic purposes [26,[62][63][64][65][66][67]. Furthermore, other research has focused on designing suitable trails for therapeutic activities within forest environments [68].…”
Section: Relevant Areas Of Forest Therapy Research In Europementioning
confidence: 99%
“…This entails assessing the air quality, analyzing the composition of vegetation and the volatile organic compounds released by plants, and investigating sustainable management strategies for forests used for therapeutic purposes [26,[62][63][64][65][66][67]. Furthermore, other research has focused on designing suitable trails for therapeutic activities within forest environments [68].…”
Section: Sustainability and Environmental Aspectsmentioning
confidence: 99%
“…Careful application is required, and the methodologies' limitations should be taken into account, especially when determining the nonuse value of a service for which no market price exists (Zegeye et al, 2023). Extensive research conducted in Europe through the study Operationalization of Natural Capital and Ecosystem Services Integrated (OpenNESS) (Makovníková et al, 2023) classified the methods used for evaluating ESs into the following categories: (i) biophysical methods, which are used for mapping ESs and include matrix approaches, ecosystem modelling with InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs, E-Tree or ESTIMAP; (ii) integrated mapping-modelling approaches; (iii) land-use scoring; (iv) participatory mapping; (v) sociocultural methods for understanding social preferences or values for ESs, such as deliberative assessment methods, preference prioritization methods, multicriteria analysis methods and photo-elicitation surveys; (vi) monetary methods for estimating the economic value of services, such as preference methods, revealed preference methods and travel cost methods (Wubalem et al, 2023) or hedonic pricing methods (Aziz et al, 2023); and (vii) integrative approaches (Gobster et al, 2023). Many elements, such as the nature of the decision at hand, the merits and drawbacks of the potential approaches, and practical considerations like the quantity and quality of data and the accessibility of relevant experts, might influence the choice of approach to take in any given situation.…”
Section: Utilitarian and Nonutilitarian Approaches Of Ecosystem Valua...mentioning
confidence: 99%